Enhancing EFL Learners’ Oral Communication Skills through the Use of Drama Activities in the Classroom The Case Study of Third year LMD students and Teachers of English at Ammar Thelidji University - Boudhelaa,Khadidja; Boumous, Moufida (Faculty of Letters and Foreign Languages Department of English, 2018)
Developing oral communication skills is a desired general goal in education and a specific focus of the EFL learners. The current paper aims to investigate the effectiveness of drama EFL learners’ attitudes about enhancing their oral communication skills through the employment of drama techniques. In order to achieve this goal, a questionnaire was used as a measuring tool. It is devoted to some teachers and second year and third-year students, at the department of English, in the University of Ammar Thelidji, registered in the academic year 2017-2018. After the description and analysis of the data, the results obtained show that drama techniques are not widely used in the English Department and the teachers and students show positive attitudes towards using the drama techniques for the development of their oral communication skills